N-alkyl-[1, 1′-biphenyl]-2-sulfonamide derivatives as novel broad spectrum anti-epileptic drugs with efficacy equivalent to that of sodium valproate. Issue 17 (1st September 2017) - Tanaka, Tomoyuki; Yajima, Nana; Kiyoshi, Tomoko; Miura, Yoshiki; Iwama, Seiji
Graphical abstract: Abstract: In order to develop phenyl sulfonamides as a novel class of anti-epileptic drugs (AED) for both general and partial seizure, we initiated in vivo screening of our chemical library in the mice MES and sc-PTZ models and found compounds1 and2 as lead compounds. Optimization of1 and2 led to the discovery of compound21, which showed potent anticonvulsant effect in MES, scPTZ and rat amygdala kindling models. These findings indicate that compound21 could be a useful new broad spectrum AED like sodium valproate and provide an opportunity to struggle current therapy-resistant epilepsy.